Communication development in congenitally blind and severely vision impaired children : Principles and strategies - Blackall, Loretta. (Royal Victorian Institute for the Blind, 1990)
The impact of congenital blindness and severe visual impairment on communication development; Strategies for working with children with severe visual impairment.